2020
DOI: 10.5129/001041520x15670823829196
|View full text |Cite
|
Sign up to set email alerts
|

Do the Rich and the Poor Have Different Conceptions of Democracy? Socioeconomic Status, Inequality, and the Political Status Quo

Abstract: In this study, we investigate how socioeconomic status is related to people's commitment to liberal democracy. Based on sociological and psychological theories of social conflict and dominance, we argue that those who enjoy a more privileged position in the social hierarchy tend to develop stronger preferences for the existing social and political order. Conversely, people in underprivileged positions tend to be less supportive of that order. Hence, we expect the relationship between socioeconomic status and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…Political orientation also matters: left-wing oriented individuals are more supportive of participatory mechanisms, whereas right-wing individuals are more prone to support technocratic mechanisms (Bengtsson and Mattila, 2009;Bertsou and Pastorella, 2017). Finally, recent studies have shown that individuals who are more politically and socially marginalized are more likely to support various alternatives to the political status quo (Ceka and Magalhães, 2020), such as the increased use of referendums (Bowler and Donovan, 2019) or sortition (Vandamme et al, 2018;Bedock and Pilet, 2020).…”
Section: What Do Citizens Expect From Their Political System? Existinmentioning
confidence: 99%
“…Political orientation also matters: left-wing oriented individuals are more supportive of participatory mechanisms, whereas right-wing individuals are more prone to support technocratic mechanisms (Bengtsson and Mattila, 2009;Bertsou and Pastorella, 2017). Finally, recent studies have shown that individuals who are more politically and socially marginalized are more likely to support various alternatives to the political status quo (Ceka and Magalhães, 2020), such as the increased use of referendums (Bowler and Donovan, 2019) or sortition (Vandamme et al, 2018;Bedock and Pilet, 2020).…”
Section: What Do Citizens Expect From Their Political System? Existinmentioning
confidence: 99%
“…A first finding to be underlined within this logic concerns the effect of respondents' satisfaction with their income. Previous studies showed that citizens who were better off socio-economically support the status quo are and more reluctant regarding reforms that would reduce the role of elected politicians (Ceka and Magalhaes, 2019;Bedock and Pilet, 2020a). Our findings show a slightly different pattern.…”
Section: Who Belongs To the Different Profiles Of Citizens?mentioning
confidence: 99%
“…Recent studies comparing survey responses to register-based indicators show that surveys underestimate socioeconomic differences and differences between men and women and natives and voters with a migrant background in electoral participation (Dahlgaard et al 2019;Lahtinen et al 2019). The same observation may well apply to studies of representational preferences, particularly as the earlier research has shown that economically-disadvantaged citizens are the ones likely to be less committed to the principles of liberal democracy (Ceka and Magalhães 2019) and dissatisfied with democracy if their preferences are not reflected by democratic institutions (Han and Chang 2016).…”
Section: <A> Conclusionmentioning
confidence: 75%